Assessment of Blood Glucose and Electrolytes during Cardiopulmonary Bypass in Diabetic and Non-Diabetic Patients of Pakistan - Bilal, Muhammad (Glob J Health Sci, 2016)
INTRODUCTION: Perioperative hyperglycemia has been shown to be related to higher levels of morbidity and mortality in patients on cardiopulmonary bypass (CPB) undergoing coronary artery bypass grafting (CABG), both diabetic and non-diabetic. Blood electrolytes, like sodium, potassium, calcium, and chloride play a very important role in the normal functioning of the body and can lead to a variety of clinical disorders if they become deficient. A minimal number of studies have been conducted on the simultaneous perioperative changes in both blood glucose and electrolyte levels during CPB in Pakistan. Therefore, our aim is to record and compare the changes in blood glucose and electrolyte levels during CPB in diabetic and non-diabetic patients. MATERIALS AND METHODS: This was a prospective, observational study conducted on 200 patients who underwent CABG with CPB, from October 2014 to March 2015. The patients were recruited from the Cardiac Surgery Ward, Civil Hospital Karachi after they complied with the inclusion criteria. Repeated-measures analysis of variance (ANOVA) was used to compare the trend of the changes perioperatively for the two groups. RESULTS: There was no significant difference in changes in blood glucose between the two groups (P = 0.62). The only significant difference detected between the two groups was for PaCO(2) (P = 0.001). Besides, further analysis revealed insignificant group differences for the trend changes in other blood electrolytes (P > 0.05). CONCLUSION: Our findings highlighted that there is no significant difference in blood electrolytes changes and the increase in blood glucose levels between diabetic and non-diabetic patients.